Suppression of Inflammation in Ulcerative Colitis by Interferon-β-1a Is Accompanied by Inhibition of IL-13 Production - Mannon, Peter J. (2010)
BACKGROUND AND AIMS: Ulcerative colitis (UC) is associated with increased IL-13 production by natural killer T cells. Taking advantage of the inhibitory actions of interferon-β on IL-13 expression, this proof-of-concept study aimed to show that decreasing IL-13 production is associated with clinical improvement of UC symptoms. METHODS: Adult patients with active UC were treated with 30 μg IM interferon-β-1a weekly for 12 weeks with 6 month follow-up. Clinical response was measured by the Short Clinical Colitis Activity Index, and cytokine production was measured in peripheral blood and lamina propria mononuclear cells (LPMC) before and after treatment. RESULTS: 11 of 16 patients were clinical responders, and 4 were in remission at the end of treatment. Rectal bleeding subscores improved dramatically by Week 4 (38% with frank bleeding vs 87% pretreatment). Increased IL-13 production by LPMC T cells fell significantly in responders (690±99 vs 297±58 pg/mL p=0.015) but was unchanged in non-responders (542±83 vs 510±39 pg/mL). In addition, non-responders had significantly higher production of IL-17 and IL-6 pretreatment compared to responders. CONCLUSIONS: Interferon-β-1a induces clinical response and remission in a large subset of UC patients that is clearly associated with inhibition of IL-13 production. In addition, increased IL-17 and IL-6 production is associated with no response to interferon-β. These data provide a proof-of-concept that IL-13 is an effector cytokine in UC and should be a target for novel therapies.